Progesterone receptor expression contributes to gemcitabine resistance at higher ECM stiffness in breast cancer cell lines. - Emma Grant; Fatma A Bucklain; Lucy Ginn; Peter Laity; Barbara Ciani; Helen E Bryant (PLoS ONE, 2022)
Chemoresistance poses a great barrier to breast cancer treatment and is thought to correlate with increased matrix stiffness. We developed two-dimensional (2D) polyacrylamide (PAA) and three-dimensional (3D) alginate in vitro models of tissue stiffness that mimic the stiffness of normal breast and breast cancer. We then used these to compare cell viability in response to chemotherapeutic treatment. In both 2D and 3D we observed that breast cancer cell growth and size was increased at a higher stiffness corresponding to tumours compared to normal tissue. When chemotherapeutic response was measured, a specific differential response in cell viability was observed for gemcitabine in 2 of the 7 breast cancer cell lines investigated. MCF7 and T-47D cell lines showed gemcitabine resistance at 4 kPa compared to 500 Pa. These cell lines share a common phenotype of progesterone receptor (PGR) expression and, indeed, pre-treatment with the selective progesterone receptor modulator (SPRM) mifepristone abolished resistance to gemcitabine at high stiffness. Our data reveals that combined treatment with SPRMs may therefore help in reducing resistance to gemcitabine in stiffer breast tumours which are PGR positive.